The dual-channel sales strategy of liner slots considering shipping e-commerce platforms. (September 2021) - Sun, Heying; Lam, Jasmine Siu Lee; Zeng, Qingcheng
Highlights: The study focuses on dual-channel sales strategy decision of liner slots considering shipping e-commerce platforms. Two-stage game model is developed to design the purchasing contract under each sales channel. A win–win situation for both the shipper and the liner company can be found based on various conditions. The impacts of some parameters on the optimal performances are evaluated under the win–win channel. The results serve as managerial recommendations for liner companies to design effective shipping e-commerce platforms. Abstract: The flourishing development of e-commerce technologies has fostered the rapid development of shipping e-commerce, which has a huge development potential especially in the case of the great impact of COVID-19 on the container shipping industry. Shipping e-commerce is characterized by ensuring that the transportation contract is completed on time. While in the traditional channel, shippers may not complete the contract on time due to the overselling behavior of liner companies. However, participants usually are unfamiliar with the shipping e-commerce channel, which leads to a wait-and-see attitude. Therefore, the issue of the liner slot dual-channel sales strategy is worth tackling under two sales channels, including the ES channel (shipping e-commerce platform and spot market) and CS channel (contract and spot markets). A two-stage game model considering the overselling behavior of liner companies is constructed for each channel to analyze the shipper's ordering decision and the liner company's pricing strategy, identifying a win–win sales channel for them. The results indicate that whether a strategy is win–win depends on the demand gap between high-and low-demand seasons, the allocated capacity under each channel, and unit compensation cost. Moreover, the impacts of some parameters on the optimal performances under the win–win strategy are analyzed. The results would be conducive to both the academic research on the contract mechanism when liner companies design shipping e-commerce platforms and the practice of container slot sales strategy selection to achieve various long-term goals.